2023
DOI: 10.3390/ma16062196
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of TiO2 Nanolubricant Influence in Micro Deep Drawing of Stainless Steel SUS301

Abstract: To improve the quality of products produced from microforming, various nanolubricants have been applied in the field of micromanufacturing in recent years. In this paper, the effects of glycerol-based lubricant containing TiO2 NPs (NPs) on micro deep drawing (MDD) of austenitic stainless steel (ASS) SUS301 were studied, and the lubrication mechanism involved was discussed. The MDD experiments were conducted with the SUS301 foils under dry, 1, 2, and 4 wt% TiO2 NP lubrication conditions. The results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Using the glycerine-based nanolubricant, the pulling force could be reduced by up to 36.6%. They also found that too much nano-additive (~4 wt%) already creates a significant number of agglomerations in the lubricant, which hurts the performance of tribological systems [33]. It is important to study the effect of nano-sized TiO 2 under different loads.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using the glycerine-based nanolubricant, the pulling force could be reduced by up to 36.6%. They also found that too much nano-additive (~4 wt%) already creates a significant number of agglomerations in the lubricant, which hurts the performance of tribological systems [33]. It is important to study the effect of nano-sized TiO 2 under different loads.…”
Section: Literature Reviewmentioning
confidence: 99%